Rational Insurance Purchasing: Consideration of Contract Nonperformance - Doherty, Neil A.; Schlesinger, Harris (Quarterly Journal of Economics, 1990)
Neil A. Doherty, Harris Schlesinger; Rational Insurance Purchasing: Consideration of Contract Nonperformance*, The Quarterly Journal of Economics, Volume 105, I